Frequency and temperature dependent electric polarization, relaxation, and transport properties of Mo and W doped BaTiO3 - Md. Sarowar Hossain; Sankar Kumar Das; Md. Moniruzzaman; M.A. Hakim; M.A. Basith (Results in Physics, 2021)
In this article, we report the structural, dielectric, electronic, and transport properties of Mo and W doped BaTiO3 ceramic. The BaTiO3 (BTO), BaTi0.85Mo0.15O3 (BTMO), and BaTi0.85W0.15O3 (BTWO) samples were prepared by double sintering ceramic technique. The X-ray diffraction patterns confirmed the tetragonal phase of the perovskite structure with the P4mm space group including some extra phases in BTMO and BTWO. A relaxation peak in the real part of electric modulus M'' is observed for BTO and BTMO at 3kHz. The dielectric constants, (εr' , εr'') and loss tangent (tanδ) for all samples were measured from 300 K to 450 K under the application of 100kHz electric field and temperature dependent dielectric anomalies ensure a ferroelectric (tetragonal) to paraelectric (cubic) phase transition in all samples. BTO and BTMO crystals display between normal ferroelectric and ideal relaxor behavior while BTWO crystal approaches to ideal relaxor ferroelectric behavior identified as canonical relaxor. Moreover, solid–liquid state anisotropy during the phase transition in all samples has been illustrated in terms of Fröhlich entropy. Apart from this, in BTO and BTWO samples, the conduction mechanism is highly dominated by the frequency of applied field compared to BTMO sample. Moreover, all studied samples exhibit semiconducting behavior with positive temperature coefficient of resistance (PTCR) effect in between 300 K and 450 K. The BTMO sample with maximum PTCR peak (2.9%/K at 415K) may find suitability for temperature controlled device application.